Photovoltaic properties of ammoniated ruthenium oxychloride dye based solar cell - Fatehmulla, A.; Atif, M.; Farooq, W. A.; Aslam, M.; Yakuphanoğlu, Fahrettin; Yahia, I. S. (Natl Inst Optoelectronics, 2014)
The most promising system for photo-electrochemical cell which has attracted extensively is the mesoporous semiconductor layer based on TiO2. The micrographs of atomic force microscope have widely supported the nano-structure of TiO2 thick film on FTO glass. In this study, we have fabricated a dye sensitized solar cell based on nanostructured TiO2 to investigate the electrical characterization of ammoniated ruthenium oxychloride dye (Ruthenium Red) based solar cell. We used the solar cell with an active area of 0.234 cm(2) to measure a short circuit current density of 53 mu A/cm(2) and an open circuit voltage of 0.45 V under AM1.5. For the DSSC applications the capacitance-voltage, the conductance-voltage and the series resistance-voltage characteristics of the solar cell were recorded in a wide frequency ranges. The experimental results of the current study led to this conclusion that the photovoltaic performance of the dye-sensitized solar cell can be enhanced/improved by using numerous dyes.
Keywords: TiO2 nanostructure; Ruthenium Red; Photovoltaic properties; Impedance spectroscopy